2021
DOI: 10.1111/1462-2920.15411
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface and surface halophile communities of the chaotropic Salar de Uyuni

Abstract: Salar de Uyuni (SdU) is the biggest athalosaline environment on Earth, holding a high percentage of the known world Li reserves. Due to its hypersalinity, temperature and humidity fluctuations, high exposure to UV radiation, and its elevated concentration of chaotropic agents like MgCl 2 , LiCl and NaBr, SdU is considered a polyextreme environment. Here, we report the prokaryotic abundance and diversity of 46 samples obtained in different seasons and geographical areas. The identified bacterial community was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 77 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…This class is composed of very small-sized organisms grouped in the DPANN superphylum known as unexplored microbial dark matter ( Rinke et al, 2013 ). They are ubiquitous inhabitants of different hypersaline environments all around the world ( Jiang et al, 2007 ; Ghai et al, 2011 ; Narasingarao et al, 2011 ; Podell et al, 2013 ; Rinke et al, 2013 ; Gomariz et al, 2015 ; Ventosa et al, 2015 ; Di Meglio et al, 2016 ; Rubin et al, 2017 ), including saline soils ( Vera-Gargallo and Ventosa, 2018 ; Gómez et al, 2019 ; Martínez et al, 2021 ). Despite this worldwide distribution, only Candidatus Nanohaloarchaeum antarcticus , an aerotolerant member of the Nanohaloarchaea from Rauer 1 Lake and Club Lake in Antarctica, could be successfully reproduced in laboratory conditions to present days ( Hamm et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This class is composed of very small-sized organisms grouped in the DPANN superphylum known as unexplored microbial dark matter ( Rinke et al, 2013 ). They are ubiquitous inhabitants of different hypersaline environments all around the world ( Jiang et al, 2007 ; Ghai et al, 2011 ; Narasingarao et al, 2011 ; Podell et al, 2013 ; Rinke et al, 2013 ; Gomariz et al, 2015 ; Ventosa et al, 2015 ; Di Meglio et al, 2016 ; Rubin et al, 2017 ), including saline soils ( Vera-Gargallo and Ventosa, 2018 ; Gómez et al, 2019 ; Martínez et al, 2021 ). Despite this worldwide distribution, only Candidatus Nanohaloarchaeum antarcticus , an aerotolerant member of the Nanohaloarchaea from Rauer 1 Lake and Club Lake in Antarctica, could be successfully reproduced in laboratory conditions to present days ( Hamm et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aquatic counterpart of the microflora in hypersaline systems has been thoughtfully studied and is typically dominated by aerobic archaea and bacteria, some of which can also live as facultative anaerobes ( Oren and Trüper, 1990 ; Oren, 1991 ; Bonete et al, 2008 ; Antunes et al, 2011 ). On the other hand, the number of studies on the microflora of the more reduced submerged hypersaline sediments is very limited ( Kim et al, 2012 ; Sirisena et al, 2018 ; Vera-Gargallo and Ventosa, 2018 ; Martínez et al, 2021 ), and there is a marked lack of information on the anaerobic representatives of hyperhalophiles. The energy cost of thriving in high salt concentration may be presumed as unaffordable for anaerobic metabolisms ( Oren, 2011 ); nevertheless, information emerging from molecular ecology studies based on the small subunit rRNA gene phylogeny progressively demonstrates the existence of diverse anaerobic communities in submerged sediments ( Jiang et al, 2006 ; Vavourakis et al, 2018 ) in which most members remain uncultured.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the water activity of the Salar-de-Uyuni system (0.856-0.618; Martínez et al, 2021) straddles the currently recognized limit for cellular activity of halophilic prokaryotes (0.635; Stevenson et al, 2015). Consistent with this finding, Martínez et al (2021) identified taxa that are known to be capable of proliferating at water activities lower than that of saturated NaCl (whch is about 0.755). The Martínez et al study provides the first insights into the microbiology of an underground chaotropic habitat and reveals marked differences between surface and subsurface communities.…”
Section: 'Ecophysiology Of Extremophiles' Special Issuementioning
confidence: 61%
“…Martínez et al . (2021) carried out a study of low water‐activity and osmotically stressful chaotropic brines located at high altitude in the Salar de Uyuni salt pan (Andes Mountains). At the surface, microbes are also exposed to high ultraviolet radiation (primarily UV‐A) and considerable fluctuations in temperature and relative humidity.…”
Section: ‘Ecophysiology Of Extremophiles’ Special Issuementioning
confidence: 99%
See 1 more Smart Citation